What is the socialists’ nation? Proposals and dilemmas of the Liga de Acción Política as a left-wing nationalist project in Colombia - Núñez Espinel, Luz Angela (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article analyses how the Colombian socialists of the Liga de Acción Política (LAP) tried to justify their existence in the national political sphere, as a Marxist and nationalist party; an exercise that requires a convergent rereading of these two ideological currents. The documental corpus analysed is drawn mainly, but not exclusively, from the newspaper Acción Política, which was the means of expression of the LAP. It is argued that the effort to «nationalize» socialism temporarily enhanced the left and implied an attempt to symbolically dispute nationalism, which the Conservative Party had constructed on the basis of Hispanist values. However, the process of inventing a historic tradition between left and nation ended up favoring the dependence of socialism on liberalism, not only as an ideology, but also as a party.